Ti2CTx MXene‐based all‐optical modulator. Issue 3 (9th December 2019) - Yi, Jun; Li, Jie; Huang, Shuohan; Hu, Longyu; Miao, Lili; Zhao, Chujun; Wen, Shuangchun; Mochalin, Vadym N.; Rao, Apparao M.
Abstract: MXenes, a new class of 2D transition metal carbides, nitrides, and carbonitrides, have attracted much attention due to their outstanding properties. Here, we report the broadband spatial self‐phase modulation of Ti2 CT x MXene nanosheets dispersed in deionized water in the visible to near‐infrared regime, highlighting the broadband nonlinear optical (NLO) response of Ti2 CT x MXene. Using ultrafast pulsed laser excitation, the nonlinear refractive index n 2 and the third‐order nonlinear susceptibility χ monolayer 3 of Ti2 CT x MXene were measured to be ∼10 −13 m 2 /W and ∼ 10 −10 esu, respectively. Leveraging the large optical nonlinearity of Ti2 CT x MXene, an all‐optical modulator in the visible regime was fabricated based on the spatial cross‐phase modulation effect. This work suggests that 2D MXenes are ideal broadband NLO materials with excellent prospects in NLO applications. Abstract : In this work, the broadband spatial self‐phase modulation effect of metallic Ti2CTx MXene has been investigated in the visible to near‐infrared regime. Under ultrafast pulsed laser excitation, a large third‐order susceptibility of Ti2CTx MXene was measured, which highlights its excellent potential use in nonlinear optical devices. Furthermore, a MXene‐based all‐optical modulator was demonstrated based on the spatial cross‐phase modulation effect.